Perilaku Bullying pada Anak Usia Sekolah Dasar di Desa Gribig, Kudus - Novia Aristiani; Mohammad Kanzunnudin; Nur Fajrie (Journal Prakarsa Paedagogia, 2021)
This study aims to analyze The Bully of elementary school students in Gribig village. This research uses narative of qualitative research methods. The data collection technique used in this study was data triangulation, namely observation, in-depth interviews and documentation. The subjects studied were students, parents and teachers in Gribig village. The data analysis technique used is data reduction, data presentation and conclusion. The forms of bullying include physical, verbal, and psychological or mental behavior. The explanation of the forms of bullying in Gribig Village is among others: (1) Verbal bullying is a form of bullying behavior that is captured through the sense of hearing. Verbal bullying includes calling, yelling, insulting, humiliating in public and slandering. (2) Physical bullying is a form of bullying behavior that can be seen directly by the sense of sight due to direct contact between the behavior and the victim. (3) Physical bullying is a form of bullying behavior that can be seen directly by the sense of sight due to direct contact between the behavior and the victim. Researchers categorized the characteristics between child victims of bullying and children of bullies in Gribig Village, as follows: (1) Children who are targets of bullying tend to be passive, submit to others, feel unworthy and will not retaliate if they receive unpleasant treatment. In addition, children who are anti-aggressive behavior, withdraw from social interactions, are socially quiet, and easily anxious are included in the child victims of bullying. (2) Children who do bully behavior toward other children. The characteristics of bullies include being physically stronger than other students, less able to understand and feel what others feel, having a positive attitude of violence, being aggressive towards peers and adults, being close to the perpetrator, being less able to control themselves, not being willing to obey social norms, often coercive victims, come from a violent authoritarian family, and there is a history of bullying.